A New Reactive Atom Plasma Technology (RAPT) for Precision Machining: the Etching of ULE® Surface - Fanara, C.; Shore, Paul; Nicholls, John R.; Lyford, N.; Kelley, J.; Carr, J.; Sommer, P. (John Wiley & Sons, Ltd, 2006)
Results on reactive atom plasma etching performed on ULE® (Corning Ultra Low Expansion) glass samples at atmospheric pressure are presented for the first time. A reactive atomic plasma technology (RAPT®), has been developed by RAPT Industries and employed for the finishing of optical surfaces. An atmospheric pressure argon inductively coupled plasma (ICP) excites a reactive gas injected through its centre. The plume of hot neutral excited species reacts at the substrate yielding controlled and repeatable trenches. In the case of ULE a material removal (up to 0.55 mm3/s) is obtained without pre-heating the samples. Among the factors influencing the results, an increase in gas concentration at the same power does not change the sample temperature, indicating that thermo- chemical effects do not influence the removal rates. Due to the plasma constructive constrains, increasing the gas concentration is more practical and of wider effect than increasing the power. The benefits of the process are illustrated and the extension of the technology to large optical surfaces discusse
Keywords: Machining; Plasma technology; Surface engineering